Tehničko-tehnološki aspekt djelovanja PTT prometa u turizmu - HAVOIĆ, Štefica (Promet - Traffic&Transportation, 2026)
ENGINEERING AND TECHNOLOGICAL ASPECT OF POSTAL TRAFFIC IN TOURIST INDUSTRY This paper reiterates the significance of engineering/technological aspect in attaining an optimum work process in postal exploitation and draws the attention to the functional discrepancy of tourist industry and postal capacities. The author advocates the requirement of an as timely as possible introduction of new engineering/technological practical propositions towards a higher-quality provision of services in tourist industry and the need for major (re)constructions of postal facilities.